REPRESENTASI SOSIALISME DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER (SOCIALISM AS REFLECTED IN PRAMOEDYA ANANTA TOER’S NOVEL BUMI MANUSIA) - Jihaduddin Akbar (Universitas Lambung Mangkurat, 2023)
AbstractSocialism As Reflected In Pramoedya Ananta Toer’s Novel Bumi Manusia. Literature use to bring out the deepest desire of a writer. Literature appear as result of inner turmoil of a writer who try to see the world from his point of view, then literature be a messenger to public. Pramoedya Ananta Toer as a writer try to inculcate his wild ideas in to a brilliant creation be entitled Bumi Manusia. In Buru Tetralogy, this novel is a beginning of seeding the maturity of character named Minke, learning process, seeking knowledge, and sharpen his mind. describe the representation of socialism in the novel Bumi Manusia by Pramoedya Ananta Toer. This research is a qualitative descriptive study using genetic structuralism as a technical analysis. The data sources of this research come from sentences that represent socialism in the fields of education, law, and gender in the novel Bumi Manusia by Pramoedya Ananta Toer. Overall, incident in Bumi Manusia Novel is protest form to colonial injustice practice in Hindia Belanda.Key words: reflected, genetic-structuralism, socialism, education, law, genderAbstrakRepresentasi Sosialisme dalam Novel Bumi Manusia karya Pramoedya Ananta Toer. Sastra muncul sebagai hasil pergolakan batin seorang sastrawan yang mencoba melihat dunia dari sudut pandangnya, sastra kemudian menjadi penyampai pesan pada masyarakat. Pramoedya Ananta Toer sebagai seorang sastrawan mencoba menanamkan gagasan-gagasan liarnya ke dalam salah satu karya cemerlang berjudul Bumi Manusia. Dalam Tetralogi Buru, novel ini merupakan awal penyemaian kedewasaan tokoh Minke, proses belajar, mencari ilmu pengetahuan, serta menajamkan pikiran. Penelitian ini bertujuan untuk mendeskripsikan representasi sosialisme dalam novel Bumi Manusia karya Pramoedya Ananta Toer. Penelitian ini merupakan penelitian deskriptif kualitatif dengan menggunakan strukturalisme genetik sebagai teknis analisis. Sumber data penelitian ini berasal dari kalimat-kalimat yang merepresentasikan sosialisme dalam bidang pendidikan, hukum, dan gender pada pada novel Bumi Manusia karya Pramoedya Ananta Toer. Secara keseluruhan kejadian-kejadian dalam novel Bumi Manusia merupakan bentuk protes pada praktik ketidakadilan kolonial di Hindia Belanda.Kata-kata kunci: representasi, strukturalisme-genetik, sosialisme, pendidikan, hukum, gender